2002
DOI: 10.1016/s0167-4889(02)00261-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein import into and across the mitochondrial inner membrane: role of the TIM23 and TIM22 translocons

Abstract: Import of nuclear-encoded mitochondrial proteins requires the action of at least two different import machines, called translocons, in the mitochondrial inner membrane (IM). The TIM23 complex mediates the translocation of proteins into the mitochondria matrix, whereas the TIM22 complex is required for the insertion of polytopic proteins into the IM. While the two translocons are distinct and composed of separate subunits, the essential reactions in each complex are carried out by homologous proteins. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 81 publications
1
102
0
1
Order By: Relevance
“…However, Taz1 could be imported into yeast mitochondria independent of the inner membrane potential. Because protein translocation across the inner membrane strictly requires the ⌬ , this finding indicated that the protein was not transported across the inner membrane (Neupert, 1997;Jensen and Dunn, 2002;Koehler, 2004;Rehling et al, 2004). This was corroborated by cell fractionation analyses, which showed that Taz1 was an integral membrane protein of the outer mitochondrial membrane that exposed its soluble Cterminal domain into the intermembrane space.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, Taz1 could be imported into yeast mitochondria independent of the inner membrane potential. Because protein translocation across the inner membrane strictly requires the ⌬ , this finding indicated that the protein was not transported across the inner membrane (Neupert, 1997;Jensen and Dunn, 2002;Koehler, 2004;Rehling et al, 2004). This was corroborated by cell fractionation analyses, which showed that Taz1 was an integral membrane protein of the outer mitochondrial membrane that exposed its soluble Cterminal domain into the intermembrane space.…”
Section: Discussionmentioning
confidence: 82%
“…Dissociation of the membrane potential (⌬ ) before import by the addition of the K ϩ -ionophore valinomycin in the presence of K ϩ in the buffer did not affect transport of the precursor to a protease-protected location ( Figure 1B, lane 6). Because protein transport across the inner mitochondrial membrane depends on ⌬ (Neupert, 1997;Jensen and Dunn, 2002;Koehler, 2004;Rehling et al, 2004), we concluded that Taz1 was not transported across the inner membrane.…”
Section: Import Of Taz1 Into S Cerevisiae Mitochondriamentioning
confidence: 90%
See 1 more Smart Citation
“…The pathways along which these proteins are sorted in the IMS are diverse (1)(2)(3)(4)(5). Precursors of proteins containing cleavable matrix targeting sequences followed by transmembrane segments are initially using the general import pathway mediated by the TIM23 (translocase of the inner membrane 23) complex until the transmembrane segment reaches the inner membrane where it undergoes translocation arrest.…”
mentioning
confidence: 99%
“…In the first of these translocons, Tim23 forms a narrow channel across the inner membrane wide enough to allow passage of a single unfolded polypeptide, in a process energized by the membrane potential and the ATP-regulated actions of matrix-localized mitochondrial hsp70. (23)(24)(25) In the Tim22-based TIM translocon, polytopic membrane proteins are transferred through a Tim23-sized channel formed by Tim22, (26) integrating each successive transmembrane domain that it encounters into the membrane (27) by a mechanism that relies on the membrane potential alone. Proteins destined to cross the chloroplast inner membrane travel through the TIC translocon, although the working of this translocon are presently not well understood.…”
Section: Introductionmentioning
confidence: 99%